Part 2 – N^4 = 2(A^4) + B^4 + 2(C^4)

Previous blog:   A^4 + B^4 + C^4 + D^4 + E^4 = N^4

for   $N \; \leq \; 100$

$5^4 \; = \; 2(2^4) \; + \; 3^4 \; + \; 2(4^4)$

$10^4 \; = \; 2(4^4) \; + \; 6^4 \; + \; 2(8^4)$
$15^4 \; = \; 2(6^4) \; + \; 9^4 \; + \; 2(12^4)$
$20^4 \; = \; 2(8^4) \; + \; 12^4 \; + \; 2(16^4)$
$25^4 \; = \; 2(10^4) \; + \; 15^4 \; + \; 2(20^4)$
$30^4 \; = \; 2(12^4) \; + \; 18^4 \; + \; 2(24^4)$
$35^4 \; = \; 2(14^4) \; + \; 21^4 \; + \; 2(28^4)$
$40^4 \; = \; 2(16^4) \; + \; 24^4 \; + \; 2(32^4)$
$45^4 \; = \; 2(18^4) \; + \; 27^4 \; + \; 2(36^4)$
$50^4 \; = \; 2(20^4) \; + \; 30^4 \; + \; 2(40^4)$
$55^4 \; = \; 2(22^4) \; + \; 33^4 \; + \; 2(44^4)$
$60^4 \; = \; 2(24^4) \; + \; 36^4 \; + \; 2(48^4)$
$65^4 \; = \; 2(26^4) \; + \; 39^4 \; + \; 2(52^4)$
$65^4 \; = \; 2(4^4) \; + \; 63^4 \; + \; 2(32^4)$
$70^4 \; = \; 2(28^4) \; + \; 42^4 \; + \; 2(56^4)$
$75^4 \; = \; 2(30^4) \; + \; 45^4 \; + \; 2(60^4)$
$80^4 \; = \; 2(32^4) \; + \; 48^4 \; + \; 2(64^4)$
$85^4 \; = \; 2(12^4) \; + \; 77^4 \; + \; 2(54^4)$
$85^4 \; = \; 2(34^4) \; + \; 51^4 \; + \; 2(68^4)$
$90^4 \; = \; 2(36^4) \; + \; 54^4 \; + \; 2(72^4)$
$95^4 \; = \; 2(38^4) \; + \; 57^4 \; + \; 2(76^4)$

$100^4 \; = \; 2(40^4) \; + \; 60^4 \; + \; 2(80^4)$

Contributor:   Paul